The Influence of Transformational Leadership on Performance Through Organizational Commitment as an Intervening Variable on Non-Permanent Employees of DPM-PTSP Jambi Province - Zikri, M.; Sumarni, Sumarni; Tialonawarmi, Feny (Asian Journal of Management Analytics, 2025)
This research aims to analyze the influence of transformational leadership on performance through organizational commitment as an intervening variable for non-permanent employees of the DPM-PTSP Jambi Province. The method used is quantitative analysis with a population and sample of all non-permanent employees totaling 40 respondents. Data collection was carried out using a Likert scale-based questionnaire, and analysis was carried out using Structural Equation Modeling (SEM) techniques based on Partial Least Square (PLS) via SmartPLS 3 software. The results of the research showed that: (1) transformational leadership has a positive and significant effect on employee performance, (2) transformational leadership has a positive and significant effect on organizational commitment, (3) organizational commitment has a positive and significant effect on employee performance, and (4) organizational commitment as an intervening variable has a positive and significant effect between transformational leadership and employee performance.